ANALYSIS OF BANKRUPTCY PREDICTIONS IN TOBACCO COMPANIES USING ALTMAN Z-SCORE METHOD BASED ON 2013-2018 FINANCIAL ANNUAL REPORTS - Wicaksono, Kasman; Musa, Purnawarman; Anggraeini, Apriana (JAFFA, 2021)
This study aims to analyze the financial health condition of a company using the Altman Z-Score method in predicting the potential bankruptcy of a tobacco-producing company in 2013-2018, which is listed on the Indonesia Stock Exchange. The type of data used in this study is obtained from the website www.idx.co.id for five consecutive years. The results showed that from 2013 until 2018, this tobacco-producing company was in the healthy and low-risk category. The value of the total assets variable is the key to changes in its health condition if it changes its value. The results of this study are expected that the company can continue to fulfill its obligations to investors and creditors and manage assets to increase sales in generating profits.